Understanding The Process of Intercultural Communication in Working Group: Research on Indonesian AIESEC Members Who Have Duty on Abroad. - Yuliana Harianja; Dr. Turnomo Rahardjo (Interaksi Online, 2016)
The numbers of Indonesian people who work and living abroad are increasing. There are a lot of opportunities for young people to be able to have challenging working experience in international organization with people from different cultural background. Unfortunately, to be able to adapt to the group consist of people from diverse cultural background, it is required to have a good competence in intercultural communication. Conflict becomes a common things for people that work in a group with high levels of cultural diversity. This research aims to know and to describe the intercultural communication process in working group of Indonesian AIESEC members who have duty on abroad. This research is qualitative research and use phenomenology approach. The theories used in this research are Effective Intercultural Workgroup Theory, Intercultural Adaptation Theory, and Anxiety/ Uncertainty Management Theory. The results of this study indicate that the creation of an effective intercultural communication is influenced by internal and external factors. Internal factors include the knowledge and experience of intercultural communication, expectations and self-disclosure. While external factors include the level of cultural differences and values within the organization. Effective communication will result in job satisfaction were seen from the positive relationships and the development of the individual personally and professionally. Recommendations can be given for future research is to conduct research on intercultural communication in work groups with more attention to the background of the organization and age range of research subjects. Background of different organizations and a wider age range allows for the communication process is more complex in the working group.